The calibration of a transmission dynamometer, and tests with same on engine lathe - Dearborn, Charles Sumner (My University, 1904)
Introduction: A transmission dynamometer is an instrument by means of which the power in a rotating shaft may be measured during its transmission through a belt or other connection to another shaft, without being absorbed. The dynamometer in question is of the Brigg's belt type, and was built by the Mechanical Engineering Department of the Kansas State Agricultural College, from drawings made by the author in 1902. Preliminary trials showed a stiffness in the action of the weighing mechanism that precluded reliable results, and changes in the construction were accordingly made for the purpose of doing away with this defect.
Citation: Dearborn, Charles Sumner. The calibration of a transmission dynamometer, and tests with same on engine lathe. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Dynamometer; Mechanics; Dynamics; Statics; Engineering; Mechanical Engineering; Theses